Comportamento fenotípico e genotípico e desenvolvimento de cultivares híbridas de manjericão - Santana, Aléa Dayane Dantas de (2014)
Basil (Ocimum basilicum L.) is a medicinal, aromatic and spicy species, which has wide variability and consecutively potential for obtaining new cultivars that add characters of interest. To obtain information about the genotype it is necessary to use phenotypic and genetic parameters, since they may estimate the genotypic behavior from the phenotype. Thus, the aim of this work was to evaluate the phenotypic and genotypic performance of basil hybrids and cultivars grown in four crop years, as well as developing new hybrid cultivars. The experiments were conducted in a randomized block design, with three replications. Five hybrids and four parental cultivars constituted the treatments. We evaluated agronomic (dry weight of aerial part, essential oil content and yield) and chemical (linalool, 1,8-cineol, neral, geranial and (E)-methyl cinnamate content in the essential oils) characteristics. The clustering of the means was performed, and the parameters were estimated: genotypic quadratic component ; residual variance ; genotypic coefficient of determination ; coefficient of genetic variation ; coefficient of environmental variation ; ratio, and coefficient of phenotypic and genotypic correlation . All variables expressed high percentages of (higher than 90 %), (higher than 30 %) and ratio (higher than 2 %). The greatest genotypic correlation occurred between neral and geranial ( ranging from 0.949 to 1.005). Most of the variation among the studied variables resulted from the genetic variation, which resulted in differentiated inheritance of characters, agronomic and chemical performance. Linalool was the main compound of most genotypes. The hybrid Cinnamon x Maria Bonita had the highest dry weight of aerial part (90.72 g plant-1) and essential oil yield (2.37 ml plant-1) and contained two main components, methyl cinnamate (41.93 %) and linalool (34.92 %). The hybrid Sweet Dani x Cinnamon presented as a main component (E)-methyl cinnamate (60.15 %), with content superior than its parental ´Cinnamon (47.67 %), besides exhibiting 16.01 % of linalool, which was absent on its parental ´Sweet Dani´. The main component of the hybrid Sweet Dani x Maria Bonita were linalool (58.83 %), as well as geranial (15.20 %) and neral (11.46 %), which were absent on its parental ´Maria Bonita´. The hybrids Sweet Dani x Maria Bonita, Cinnamon x Maria Bonita e Sweet Dani x Cinnamon, were distinct in new hybrid cultivars, denominated: ´Vitória´, and ´Norine´ and ´Natalina´, respectively.